(untitled) (Latakia University Journal -Biological Sciences Series, 2013)
This research was aimed to study a gross chemical composition of Avocado fruits and seeds, and to known physicochemical characteristics of its oil, and its fatly acid composition. The data indicated that its fruits contained (12.4%) oil , while seeds contained lower amounts of oil which reached (1.92%) dry weight basis , and the moisture content of seeds reached (52.5%) , and acid value reached (1.6 and 4.3 mg KOH/g) at fruit and seed oils respectively , Avocado fruits oil contained (77.77%) unsaturated fatly acid , and (21.77%) saturated , and iodine value obtained in our study ) 77-84 g I/100 g) of fruits oil and ( 45.78 g I/100 g) of seeds oil confirming the unsaturated nature of these oils. Also Avocado fruits and seeds oil possessed a low peroxide value comparison others (3.71 , 2.2 Meq/kg oil) respectively , The data also indicated that its seeds contained (52.5%) moisture , (7.45%) grude fibers ,(8.53%) sugars , (4.69%) pure protein , (2.34%) ash , and high percentage of starch (59.3%) dry weight basis .